The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1590/1806-9282.66.s1.75
|View full text |Cite
|
Sign up to set email alerts
|

HIV-related nephropathy: new aspects of an old paradigm

Abstract: SUMMARY The scenario of infection by the human immunodeficiency virus (HIV) has been undergoing changes in recent years, both in relation to the understanding of HIV infection and regarding the treatments available. As a result, the disease, which before was associated with high morbidity and mortality, is now seen as a chronic disease that can be controlled, regarding both transmission and symptoms. However, even when the virus replication is well controlled, the infected patient remains at high risk of devel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 17 publications
(11 reference statements)
0
10
0
2
Order By: Relevance
“…Indeed, ART contributes a great deal to changing the incidence and spectrum of HIV-associated kidney diseases. The current prevalence of HIV-associated nephropathy (HIVAN) is approximately 20% among HIV-infected patients [ 78 ]. Therefore, there is a reason to believe that HIV-associated renal lesion can be attributed to the following hematological abnormalities: fibrinogen and coagulation factor VIII, vWF, and deficiency of antithrombin III, PC, and PS [ 79 , 80 ].…”
Section: Pathogenic Factors Of Hiv-associated Thrombosismentioning
confidence: 99%
“…Indeed, ART contributes a great deal to changing the incidence and spectrum of HIV-associated kidney diseases. The current prevalence of HIV-associated nephropathy (HIVAN) is approximately 20% among HIV-infected patients [ 78 ]. Therefore, there is a reason to believe that HIV-associated renal lesion can be attributed to the following hematological abnormalities: fibrinogen and coagulation factor VIII, vWF, and deficiency of antithrombin III, PC, and PS [ 79 , 80 ].…”
Section: Pathogenic Factors Of Hiv-associated Thrombosismentioning
confidence: 99%
“…However, it remains elusive as to whether these factors work independently or in a synergistic manner. It is believed that HIV-associated immunodeficiency exerts its cancer-predisposing effects via two primary mechanisms [ 1 ]: reduced body's ability to clear and control oncogenic virus infections and [ 2 ] reduced immune surveillance of malignant cells [ 92 , 106 ]. As evidence accumulates, it has been found that HIV itself may exert direct oncogenic effects via its Tat protein [ 107 ] involving multifaceted mechanisms including synergism with other oncogenic viruses [ 107 ], blockage of tumour suppressor gene function [ 108 ] and disruption of cell cycle regulation [ 109 ].…”
Section: Hiv-regulated Lncrnas Promote Carcinogenesismentioning
confidence: 99%
“…Human immunodeficiency virus-1 (HIV-1) infection is a crucial etiological factor for various non-communicable diseases, which include HIV-associated nephropathies [ 1 , 2 ], cardiomyopathies [ 3 ] and cancer [ 4 ]. HIV-1 contributes to cancer development directly through oncogenic effects of HIV proteins, such as Trans -activator of transcription (Tat) and indirectly through immunosuppression and promiting coinfections by other oncogenic viruses [ [5] , [6] , [7] , [8] ].…”
Section: Introductionmentioning
confidence: 99%
“…The presence of APOL1 high-risk genotypes, comprising any combination of two APOL1 kidney risk alleles, increases the risk for several kidney diseases compared with APOL1 low-risk individuals (defined as those carrying zero or one APOL1 kidney risk allele). These diseases include NDRD, hypertensionattributed (HA-APOL1) associated nephropathy, FSGS, HIV-associated nephropathy [26], focal global glomerulosclerosis with interstitial and vascular changes (overlapping with the pathologic pattern formerly termed arterionephrosclerosis), sickle cell nephropathy, lupus nephritis associated with collapsing glomerulopathy and unexplained ESKD [27]. We know that analysis of the APOL1 high-risk genotypes in the African-American study of kidney disease in hypertension demonstrated that APOL1 high-risk individuals with hypertension and reduced eGFR tended to have heavier proteinuria and faster GFR loss compared with APOL1 low-risk genotypes in African ancestors.…”
Section: оригінальні наукові роботиmentioning
confidence: 99%
“…Transplantation of a kidney from a healthy living donor with two APOL1 nephropathy risk variants has been associated with FSGS with early allograft failure in recipients as well as subsequent ESKD in the donor [32]. At present, some physicians are testing potential living donors for APOL1 risk alleles before kidney donation [27,33].…”
Section: оригінальні наукові роботиmentioning
confidence: 99%